The Implementation of Project Based Learning in Blended Learning System to Improve English Speaking Skill of Polytechnic Students - Ariani, Desti; Hidayat, Ade; Girikallo, Adrianus Surianto (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
This Classroom Action Research aims to determine the improvement in students' English speaking skill by implementing Project Based Learning in a Blended Learning system. This model of learning was conducted in two cycles consisting of four meetings in each of the cycle. The research began with a pre-test to determine initial speaking skills and language aspects which became the weaknesses of Polytechnic students in speaking English. The results of the pre-test then became the basis for implementing the Project Based Learning model. Online learning was conducted by using online media to observe the process of projects making and to submit those speaking projects which were regarded as post-test at the same time. Face-to-face learning, on the other hand, was carried out to discuss the learning topics before the speaking project assignment. The results of the study showed an improvement in students' English speaking skills after the implementation of Project Based learning. In the pre-test, the average score of students' speaking skills was only 58.7. In post-test 1 of cycle 1, the average increased to 63.5 and in post-test 2 of cycle 2 it increased to 70.1. In addition, the study revealed that Project Based Learning also succeeded in changing the students’ learning attitude and in promoting students’ creativity